Sistem Pendukung Keputusan Pada Rekomendasi Pasangan Hidup Dengan Simple Additive Weigthing - Dewi Destinasari; Dudih Gustian; Sudin Saepudin (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
The life partner is one of the grace that brings a person to perfect his life, in Islam every one of his people created in pairs but the way to find the spouse certainly varies. A work of this modern technology impacts the search field of a live spouse the role of an information system is crucial to provide fast, precise and accurate information according to what is expected. The development of information systems in the Internet world aims to provide ease in the online arranged system. In this research will be developed a type of information system, decision support system, especially for recommendations on the criteria of live couples using the method of Simple Additive Weigthing (SAW), this system has the use of Effective and suitable for workers who have many activities and are difficult to take the time to interact with their opponents in an intense manner. The purpose of this research is to create a Website based application. In the mention of this information System program using Simple Additive Weighting method, the test is carried out using questionnaire data that is shared to users and IT experts and get the result of agreeing to build a system with Respondents 54.4% by IT experts and 65.4% by users. This application can be used as a consideration in determining the decision for prospective spouse recommendation.